Stroke performance in high-level Spanish wheelchair tennis players - Sanchez-Pay, A.; Torres-Luque, G.; Sanz-Rivas, D. (Revista Internacional de Ciencias del Deporte, 2017)
The aim of this study was to analyse shot selection in a wheelchair tennis (WT) tournament, comparing winning and losing players and evaluating the outcome of strokes. Sixteen men`s singles WT matches (comprising a total of 5,720 strokes) were analysed. Each match was recorded and the following variables were analysed: services, returns, groundstrokes and net shots. Additionally, all strokes were coded according to type of point (non-game point opportunity, NGO; game point opportunity, GO), outcome (error; rally; winner) and set outcome (winner; loser). A Z-test was used to assess differences between winning and losing players and between NGOs and GOs. The results showed that WT players make more errors (19%) than winning strokes (10.6%). Service and return shots make up about 55% of shots played during a point and volleys and smashes are infrequent (2.1%). Winning players hit more winners on service, return and groundstrokes than losing players. At the net losing players hit more winners than winning players, although they also made more errors. The critical situation (GO) could be not affect on game actions of WT points. These results and the differences between performances should be taken into consideration by wheelchair tennis coaches.